2023
DOI: 10.1002/anie.202218742
|View full text |Cite
|
Sign up to set email alerts
|

One‐Dimensional Covalent Organic Frameworks for the 2e Oxygen Reduction Reaction

Abstract: Two-dimensional covalent organic frameworks (2D COFs) are often employed for electrocatalytic systems because of their structural diversity. However, the efficiency of atom utilization is still in need of improvement, because the catalytic centers are located in the basal layers and it is difficult for the electrolytes to access them. Herein, we demonstrate the use of 1D COFs for the 2e À oxygen reduction reaction (ORR). The use of different four-connectivity blocks resulted in the prepared 1D COFs displaying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 55 publications
(1 reference statement)
0
29
0
Order By: Relevance
“…reported 1D COFs based on 4,4′-(2,2-diphenylethene-1,1-diyl) dibenzaldehyde (TPEDH) linkers (named PYTA-TPEDH-COF and TPETA-TPEDH-COF) for electrochemical H 2 O 2 production with good performance. [166] Among them, PYTA-TPEDH-COF showed the best selectivity for H 2 O 2 production (85.8%) and TOF (0.051 s −1 ) at 0.2 V. Li et al reported an ionic covalent organic polymer (BPyTTz-COP:X) (X = Br − , F − , Cl − or I − ), which was formed by the conjugation of viologen with electron withdrawing thiazolo [5,4-d]thiazole (TTz). [167] BPyTTz-COP: F exhibited the highest H 2 O 2 selectivity (98.5%), high current efficiency (97.2%), and good stability (>10 h).…”
Section: Electrocatalysts Of 2e − Orr Processmentioning
confidence: 99%
“…reported 1D COFs based on 4,4′-(2,2-diphenylethene-1,1-diyl) dibenzaldehyde (TPEDH) linkers (named PYTA-TPEDH-COF and TPETA-TPEDH-COF) for electrochemical H 2 O 2 production with good performance. [166] Among them, PYTA-TPEDH-COF showed the best selectivity for H 2 O 2 production (85.8%) and TOF (0.051 s −1 ) at 0.2 V. Li et al reported an ionic covalent organic polymer (BPyTTz-COP:X) (X = Br − , F − , Cl − or I − ), which was formed by the conjugation of viologen with electron withdrawing thiazolo [5,4-d]thiazole (TTz). [167] BPyTTz-COP: F exhibited the highest H 2 O 2 selectivity (98.5%), high current efficiency (97.2%), and good stability (>10 h).…”
Section: Electrocatalysts Of 2e − Orr Processmentioning
confidence: 99%
“…[24] Up to now, 1D COFs still very rare and only few examples are reported. [25][26][27][28] Boron-dipyrromethene (BODIPY) dyes are one of the most versatile fluorophores with excellent visible-light absorption ability, thermal and photochemical stabilities, high fluorescence quantum yields, and chemical robustness. [29,30] These photophysical and chemical properties of BODIPY attracted tremendous attentions and they can be widely used in photocatalysis, bioimaging, sensing and luminescent devices.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extremely high anisotropy and the entropy‐driven random packing of organic chains, the synthesis of 1D COFs are filled with huge challenge [24] . Up to now, 1D COFs still very rare and only few examples are reported [25–28] …”
Section: Introductionmentioning
confidence: 99%
“…[3] Among other applications, the COFs can catalyze oxygen reduction reaction (ORR), oxygen evolution reaction, hydrogen evolution reaction, H 2 O 2 synthesis and carbon dioxide reduction by incorporating catalytic metal ions into the knots or immobilized along the porous surfaces. [4] The ORR is a key reaction in energy conversion technologies including fuel cells and metal-air batteries. [5] To achieve highly active catalysts towards ORR, 2D materials (metallenes and transition metal nitrides) and carbon supported metal sites have been widely explored.…”
mentioning
confidence: 99%